2018
DOI: 10.1109/lra.2017.2724140
|View full text |Cite
|
Sign up to set email alerts
|

A Pneumatic Artificial Muscle Manufactured Out of Self-Healing Polymers That Can Repair Macroscopic Damages

Abstract: Pneumatic muscles are mostly constructed out of flexible membranes and are implemented in a wide range of robotic applications. In these soft materials, perforations are often caused by overpressuring of the muscles and wear. In many cases this leads to limited numbers of actuation cycles. In this paper, pleated pneumatic artificial muscles were developed, whose membrane is constructed out of self-healing polymer. This allows for the complete healing of microscopic and macroscopic damages through a mild heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…There are several ways the gelation (solidification) of the DA materials can be improved. In this study, a six-functional furan compound (FT5000) is used, which has a lower gel conversion x gel than the four-functional compound used in previous studies 16,17 and thus has a higher T gel and solidifies faster. Keeping all constraints in mind, the self-healing DA material DPBM-FT5000 in stoichiometric ratio (R ¼ n maleimide n furan ¼ 1) was selected for this application.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several ways the gelation (solidification) of the DA materials can be improved. In this study, a six-functional furan compound (FT5000) is used, which has a lower gel conversion x gel than the four-functional compound used in previous studies 16,17 and thus has a higher T gel and solidifies faster. Keeping all constraints in mind, the self-healing DA material DPBM-FT5000 in stoichiometric ratio (R ¼ n maleimide n furan ¼ 1) was selected for this application.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 In prior study, the authors developed the first demonstrators of selfhealing soft robotics, including soft grippers, soft hands, and artificial muscles. 16,17 These actuators have shown a recovery of up to 98% 16 after severe damage, leaving no weak spots.…”
Section: Objectivementioning
confidence: 99%
“…Thus, SHAP was used for the development of a pneumatic artificial muscle (PAM) [42] because, as previously mentioned, the main advantages of this material are: (i) its stability under ambient conditions, since the hydrogel remains soft over time without drying; (ii) its viscoelastic properties; (iii) its self-healing ability under ambient conditions without the need for an external stimulus. This last feature is a crucial advantage when compared, for instance, to the healable material reported by Terryn et al, [75] who presented a variant of PAM muscle made of Diels-Alder polymer that was able to self-heal on applying heat, i.e., an external stimulus is required for the self-healing process to be initiated (non-autonomous self-healing material).…”
Section: Development Of a Shap-based Pneumatic Artificial Musclementioning
confidence: 99%
“…The 3D printing process trapped liquid resin in the elastomer; when the robot was punctured, the excess resin was able to seal up the holes if given sufficient UV stimulus (such as direct sunlight). Terryn et al (2015Terryn et al ( , 2017a have taken a different approach to resilient pneumatic actuators by shaping self-healing polymers into inflatable chambers. In their early work, they molded a single, thin-walled cube out of a thermally responsive self-healing polymer and demonstrated its inflation capacity, even after catastrophic failure (Terryn et al, 2015).…”
Section: Inflatable Actuatorsmentioning
confidence: 99%
“…Most recently, Terryn et al (2017b) demonstrated that by patterning these cubes adjacent to one other, the extended system could be utilized as a soft robotic bending actuator capable of grasping objects. In another recent work, the researchers utilized this same self-healing material to create a pneumatically actuated artificial muscle that can contract over 10% of its length (Terryn et al, 2017a).…”
Section: Inflatable Actuatorsmentioning
confidence: 99%